Valores familiares en el proceso de enseñanza aprendizaje de los estudiantes del tercer año de educación básica de la Escuela "Sofia Alarcón de Espín" Parroquia Caracol del cantón Babahoyo, Provincia de Los Ríos - Pluas Orozco, Ivan Isaias (2019)
The family since the origin of humanity has been a fundamental piece for the development of individuals, their interaction every day makes clear, fixed and particular conditions be sown in each individual, that is where family values are present, it is in this stage from childhood to adolescence where the family exerts all its influence on the solid foundations for the subsequent formation of their descendants. In this research work we studied the influence that family values have in the development of the teaching-learning process of students in the third year of basic education, how this perception of values affects learning activities, their active participation in activities school children and the realization and presentation of their homework. For the development of the study, the non-experimental design was used, with a documentary and field modality, a descriptive, exploratory and explanatory type of research, with inductive, deductive, analytical and synthetic methods, was aimed at students of number 35, of third year of basic general education, its teacher and the institutional leader, to whom surveys and interviews were applied as techniques for collecting information that was complemented by observation. Obtaining as results that the majority of students do present family values and that these equally apply mostly in the development of school activities, this favors the application of learning strategies, but for not being the totality of students who present values It limits the teaching-learning process, presenting as theoretical proposal the realization of a didactic guide of formation in family values to the students of the third year of basic